Guarantees of Protection of Animals and Birds in Criminal Law: A Case Study of Georgia - Latsabidze, Giorgi (European Scientific Journal, ESJ, 2024)
Animals and birds play an important role in human life, and the creation of a robust legal framework for the protection of their rights has been discussed many times. To date, Article 259 of the Criminal Code of Georgia has undergone several legislative changes, none of which were fundamental. The main changes involved increasing the sentences. As seen in Article 259 of the Criminal Code of Georgia, it cannot fully enumerate all the actions for which a person can be punished. A person may commit an act against an animal and/or bird that is not explicitly punishable under criminal law. Article 259 of the Criminal Code protects animals from torture, ill-treatment, and other forms of violence, while Article 104 of the Code of Administrative Offenses addresses improper treatment. Despite the existence of these articles, it is difficult to determine whether a person’s action constitutes an administrative law violation or criminal liability. Additionally, the legislator uses such terms that make it even more difficult to solve the issue.